2005
DOI: 10.1103/physrevlett.95.235703
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Order and Phase Separation in Au-Ni

Abstract: We have measured and theoretically analyzed the diffuse scattering in the binary alloy system Au-Ni, which has been proposed as a testing ground for theories of alloy phase stability. We found strong evidence that in the alloys Au3Ni and Au3Ni2, fluctuations of both ordering- and clustering-type are competing with each other. Our results resolve a long-standing controversy on the balance of relaxation and mixing energies in this alloy system and explain recent findings of ordering in thin Au-Ni films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…However, the miscibility gap for bulk Au and Ni is such that bulk alloy formation is not possible at the temperatures employed in our study. [63] Molenbroek et al [36] have reported surface Ni-Au alloy formation on silica at a reduction temperature of 823 K. Our STEM-EDX results demonstrate a close proximity of Au and Ni on the Al 2 O 3 carrier and a possible consequence of surface Ni-Au interaction may be the depleted H 2 uptake capacity ( Table 2). The HDC of 2,4-DCP generated 2-chlorophenol (2-CP) as the partially dechlorinated product and phenol as the ultimate dechlorination product.…”
Section: Catalyst Structural Characteristicsmentioning
confidence: 62%
“…However, the miscibility gap for bulk Au and Ni is such that bulk alloy formation is not possible at the temperatures employed in our study. [63] Molenbroek et al [36] have reported surface Ni-Au alloy formation on silica at a reduction temperature of 823 K. Our STEM-EDX results demonstrate a close proximity of Au and Ni on the Al 2 O 3 carrier and a possible consequence of surface Ni-Au interaction may be the depleted H 2 uptake capacity ( Table 2). The HDC of 2,4-DCP generated 2-chlorophenol (2-CP) as the partially dechlorinated product and phenol as the ultimate dechlorination product.…”
Section: Catalyst Structural Characteristicsmentioning
confidence: 62%
“…The passivated sample was contacted with HAuCl 4 , posttreatment as above. After preparation, the sample (sieved into a batch of 75 lm average diameter) was activated in 60 cm 3 min -1 H 2 at 2 K min -1 to 603 ± 1 K, cooled to room temperature in a He flow and subsequently subjected to a temperature controlled treatment in 65 cm 3 min -1 N 2 at 50 K min -1 to 1273 ± 1 K. The latter step was necessary to generate the supported alloy as the Au-Ni miscibility gap is such that bulk alloy formation is not possible at temperatures below 1083 K [23]. The Au/Al 2 O 3 sample underwent the same annealing treatment to facilitate a direct comparison of catalytic performance with that of the alloy.…”
Section: Catalyst Preparation and Activationmentioning
confidence: 99%
“…However, there are many fewer studies dealing with the catalytic applications of Au-Ni catalysts [15,16]. One of the primary reasons lies in the fact that the bulk binary phase diagram of Au-Ni has a large miscibility gap and thus alloy formation becomes difficult at temperatures below 800°C [17,18]. On the other hand, atomic resolution scanning tunneling microscopy (STM) studies revealed that when Au is deposited onto Ni(110) or Ni(111) surfaces, Au replaces Ni in the first atomic layer to form a surface alloy [19,20].…”
Section: Introductionmentioning
confidence: 99%